Bilateral Nephromegaly in a Child with Severe Iron-Deficiency Anemia - Weizmann, Danna; Genest, Dominique S; Litalien, Catherine; Benoit, GeneviÃ¨ve (Journal of Pediatric Nephrology, 2021)
Nephromegaly in childhood can result from a wide variety of causes, yet iron-deficiency anemia has not been previously described. We report a child with severe iron-deficiency anemia associated with transient bilateral nephromegaly. We hypothesize that increased renal production of erythropoietin as well as greater cardiac output with subsequent glomerular hyperfiltration secondary to critical anemia explained the observed nephromegaly. The normalization of kidney size following resolution of anemia supports this hypothesis. Our case report suggests an additional etiology of bilateral nephromegaly in the pediatric population and thus merits attention among physicians.